Narcolepsy associated with primary temporal lobe B-cells lymphoma in a HLA DR2 negative subject. Issue 9 (September 1992) - Onofrj, M; Curatola, L; Ferracci, F; Fulgente, T
Abstract : Narcolepsy and cataplexy began one year before treatment of a left mid-temporal primary B-cells lymphoma in a HLA DR2 negative man. Treatment with radio therapy and immunosuppression induced regression of the lymphoma and disappearance of narcolepsy and cataplexy.